Gesunde Stadt: Die Assanierung der Stadt Wien (1934 - 1938) - Knauer, Birgit (2021)
From 1934 onwards, the city government provided funds to revive the construction industry and to push on with the renewal of the city. Many "outdated" and "traffic-obstructing" buildings were destroyed, facades were renovated by removing ornaments and structural elements which were then considered "worthless" and "tasteless". This book deals with a chapter of the architectural and urban history of Vienna that has thus far been neglected, examines the "healing" of the city in its dimensions as well as the parallel discussions of experts, and compares the renewal of the city of Vienna with similar developments in other European countries in the 1930s.